2004
DOI: 10.1007/s10681-004-4754-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of bacterial pectinolytic strains for improvement of hemp water retting

Abstract: Retting is the major limitation to an efficient production of textile hemp fibres. Traditional retting has been carried out by autochthonous bacterial community. Aerobic and anaerobic pectinolytic strains were isolated from hemp or flax sources and characterised. Anaerobic pectinolytic strains had a wide range of acid polygalacturonase (PG) activity, whereas aerobic isolates did not produce any acid PG activity, but only an alkalophylic one, suggesting they could play a minor role in the retting process, excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…showed cellusolytic activities. These results were in confirmation with the finding of Tamburini et al, (2004) who reported the presence of cellusolytic activities in the Pectinolytic strains that are Bacillus subtilis. Zhang et al, (2000) also found low cellulolytic activities (0.04-0.17 U/cm 3 ) of some strains used in degumming of ramie fibres.…”
Section: Identifi Cation Of Selected Retting Microbessupporting
confidence: 91%
“…showed cellusolytic activities. These results were in confirmation with the finding of Tamburini et al, (2004) who reported the presence of cellusolytic activities in the Pectinolytic strains that are Bacillus subtilis. Zhang et al, (2000) also found low cellulolytic activities (0.04-0.17 U/cm 3 ) of some strains used in degumming of ramie fibres.…”
Section: Identifi Cation Of Selected Retting Microbessupporting
confidence: 91%
“…This feature is important for strain selection because a prolonged treatment of hemp stems with cellulosolytic bacteria could otherwise result in loss of fibre strength, because of a direct attack to cellulosic fibres. On the contrary, all the pectinolytic anaerobic strains characterized so far showed a cellulosolytic activity (Tamburini et al. 2004).…”
Section: Resultsmentioning
confidence: 99%
“…An advisable feature of retting strains is the absence of cellulosolytic activity. An aerobic strain with no cellulosolytic activity was identified Tamburini et al (2004). El-Borhamy (2003) found that retting with water change every 48 hours gave the tallest fiber while, retting in streaming water gave the highest values of fiber fineness, fiber strength, fiber yield per fed.…”
Section: Introductionmentioning
confidence: 99%